Comparative study on wetting of smooth and rough silica surface by molten Sn–3.5Ag–2Ti alloys. Issue 20 (15th October 2021) - Lin, Qiaoli; Wang, Chaopeng; Xie, Kaibin; Wang, Le; Sui, Ran
Abstract: Whether the rough surface is beneficial or harmful in promoting wettability for a reactive wetting system at high temperatures remains an open question. The comparative study on the wetting of smooth and rough silica by Sn-3.5Ag–2Ti solders were carried out at 650–800 °C. Although the precipitation of wettable reaction products promotes wettability, the decrease in interfacial roughness by the precipitates makes the improvement in wettability does not reach the degree of inert system. Therefore, the rough surface is harmful in promoting wettability for a reactive wetting system. The wetting behavior can be divided into two types by temperatures: the linear spreading (650–700 °C) and the non-linear spreading (750–800 °C) which correspond to the reaction rate control mechanism and the diffusion control of Ti transport mechanism, respectively. The spreading is enhanced by using the rough substrate due to the strengthening interfacial reactivity.